Catequese no Brasil junto à pessoa com deficiência - Depizzoli, Antonio Marcos (2013)
This dissertation considers the catechetical matter in Brazil with accent to a person with disability. Keeping in mind the background of theological reflection this subject will be studied; and questions such as: "A person with disability has the right to be included in the catechetical process of faith formation?"; "The Christian tradition offers, from its biblical, theological and anthropological heritage, an itinerary that support the educational process-formation of the faith to a person with disability from the practice of Jesus?"; "What are the consequences of a catechesis of all and for all, since the word all also considers a person with disability?"; "The Church in Brazil, in his catechetical action, has been shown to be open to changes required to the evangelization of a person with disability?"; it will be contemplated. The method used is the view, illuminate and act, frequently used while doing theology in Latin America. This research aims to generate practical knowledge, that is, to address and solve specific problems; particularly here, the catechetical action and the Christian formation of a person with disability in the Church in Brazil. The technical procedure adopted here is formed of bibliographic and documentary research, drawn from materials published in books, articles, events, and the consultation some sites. The results achieved by the study are positive. Firstly, it has been found that, the catechetical pastoral model, since the Biblical-Theological Jewish-Christian tradition, with emphasis on the proclamation of the Kingdom of God accomplished by Jesus, it prepares the current understanding of the inclusion's concept. In addition, it was proved the hypothesis that the Church's catechetical activity in Brazil towards a person with disability is privileged instrument of development of the sense of community fraternally Christian. Lastly, the 2006's Fraternity Campaign and the project Affordable Church a Church of all and for all suggests revisiting the way of being and doing of Jesus and of the first Christian communities, adapting the advances of the modern world on those religious and theological bases. The research shows that it is relevant to the theological, catechetical and pastoral context of the Church dialogue with current theological and biblical hermeneutics from the perspective of a person with disability as the subject of faith, giving him visibility in theoretical Church's speech. It also contributes to the knowledge of the Church's catechetical activity in Brazil towards a person with disability and how catechesis becomes gateway to build inclusive communities. Finally, it encourages discussion of the theme, catechesis to a person with disability, as an important element in building an inclusive theology, taking into consideration the Church's moral duty to organize itself according to the archetype of inclusion